Cambridge O level Islamiyat paper 1 - Nishat, Hammad Ibn (Karachi : Bookmark publishing, 2019)
The Cambridge O Level Islamiyat Textbook for Paper 1 by Bookmark Publishing is a comprehensive resource specifically designed to help students succeed in the Paper 1 section of the O Level Islamiyat exam. With detailed coverage of Islamic beliefs, practices, and ethics, along with exam-style questions, summaries, and clear explanations, this textbook ensures that students are well-prepared for the exam. By providing a solid foundation in the core topics, it equips students with the knowledge and skills they need to perform confidently in Paper 1 of the O Level Islamiyat exam.
Keywords: Islamiyat : Textbook; O level : 3rd edition